Family and school and aggressive behaviours of youth - Zajdel, Krzysztof (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2013)
Aggressive behaviours begin to be a commonplaceness of the life of the school, with which neither family nor the school itself can cope. In relation to environmental causes, one should look for sources of such behaviours in parents and teachers. The educational process has various styles which leads to children’s various later behaviours. Peers’ influence, friends, social attitudes – they can either tone down some behaviours, or provoke a development of aggression (e.g. mitation of behaviours). I tried to analyse behaviours in my article, especially the family and the school, which are supported by the research of future teachers, and the conclusions can be surprising, but they induce reflections.
Keywords: family; school; agression; violence